2015
DOI: 10.1007/s13187-015-0963-4
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of Latinos’ Perceptions About Skin Cancer: the Role of Gender and Linguistic Acculturation

Abstract: Latinos have the highest rate of skin cancers among U.S. minorities. Despite a rising incidence of melanoma – the deadliest form of skin cancer – and greater disease burden, Latinos tend to have poor awareness of skin cancer risk factors which may inhibit preventive action. We expanded on prior work by qualitatively examining potential moderators (i.e., gender, acculturation) of skin cancer perceptions among Latinos from El Barrio in Harlem, New York. Four focus groups stratified by language (English/Spanish) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…The findings that relate to health literacy and knowledge of skin cancer risk factors corroborate what other researchers have reported on Latinos: as a larger group, they do not possess a great deal of knowledge of skin cancer or its risk factors [ 52 ]. This is further exacerbated by lower levels of health literacy, lower incomes, low levels of education, and lack of access to health insurance coverage.…”
Section: Discussionsupporting
confidence: 87%
“…The findings that relate to health literacy and knowledge of skin cancer risk factors corroborate what other researchers have reported on Latinos: as a larger group, they do not possess a great deal of knowledge of skin cancer or its risk factors [ 52 ]. This is further exacerbated by lower levels of health literacy, lower incomes, low levels of education, and lack of access to health insurance coverage.…”
Section: Discussionsupporting
confidence: 87%
“…This behavior extends to Hispanics of varying skin types 7 , and Hispanics in the United States have high sunburn rates 8 . Lower skin cancer awareness and perceived skin cancer risk have been identified as particular barriers to adequate and consistent sun protection in Hispanics 3,9-12 . Personalized genomic testing for melanoma risk may promote risk awareness and risk reduction in the general population, including Hispanics.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of oil is an important variable, since it directly affects the NE droplet size, along with its chemical and optical properties (Cavazos-Garduño et al, 2015). Stability increases with small sizes by avoiding gravitational segregation, flocculation by Brown's movement and greater system transparency; their bio-accessibility has been increased in in vitro systems when using O/W NE (Salvia-Trujillo et al, 2013). It has been reported that using polylactide-coglycolide-monomethoxy polyethylene glycol nanoparticles containing BA, where 147 nm globule sizes were obtained, increased its antitumor activity by up to 7 times in an Erlich carcinoma model (Saneja et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by a deregulation of cell growth and proliferation (Diaz-Cano, 2015). It is estimated that by 2025 the incidence per year will reach 19.3 million (Bishayee and Block, 2015) and it has been documented that melanoma-type skin cancer is associated with higher morbidity in Latino populations (Rodríguez et al, 2018). In addition, the increase in the incidence of skin cancer is mainly attributable to prolonged periods of sun exposure.…”
Section: Introductionmentioning
confidence: 99%